Impact on urban form of the new Social Housing projects developed in Costa Rica - von Breymann-Miranda, Helga (2021)
In Costa Rica, the social interest housing (VIS) projects developed in the last decade have been located in areas far from urban centers of limited access to facilities and infrastructure due to the prohibitive cost of land ownership in most central sectors of metropolitan cities. The conditions and characteristics of these contexts, available land uses (zoning), morphological configurations, continuity and contiguity between social interest housing projects and the urban pieces where they are inserted, are analyzed in this research through the study of five residential complexes developed in the Greater Metropolitan Area of Costa Rica. The projects, constructed between 2011 and 2018, were analyzed from the study of construction blueprints, cartography of the area, documentary review and analysis of secondary data. From the obtained results it is possible to identify the main difficulties arising from the morphological and typological fit that followed after the establishment of the residential complexes, as well as the contextual problems derived from the location of the projects.